2006
DOI: 10.1530/rep.1.00874
|View full text |Cite
|
Sign up to set email alerts
|

Identification of transcription factors at the site of implantation in the later stages of murine pregnancy

Abstract: Despite medical advances, preterm delivery continues to complicate 12% of all births in the United States and is a major cause of neonatal deaths. One of the reasons that preterm labor continues to be a significant problem is that very little is understood about the factors involved in normal labor. Many investigators have studied parturition in the mouse and defined essential pathways for normal labor. Prostaglandins play an essential role in mouse labor and are important in human labor as well. We examined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 72 publications
(86 reference statements)
0
11
0
Order By: Relevance
“…In mammals, GILZ has been shown to be expressed in a variety of tissues and cell types, including heart, brain, kidney, liver, lung, pancreas, spleen, muscle, uterus, mesenchymal cells, pre-adipocytes, and white and red blood cells , Berrebi et al 2003, Kolbus et al 2003, Shi et al 2003, Zhao et al 2006. However, this is the first report indicating expression of GILZ in the neuroendocrine system of any species.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…In mammals, GILZ has been shown to be expressed in a variety of tissues and cell types, including heart, brain, kidney, liver, lung, pancreas, spleen, muscle, uterus, mesenchymal cells, pre-adipocytes, and white and red blood cells , Berrebi et al 2003, Kolbus et al 2003, Shi et al 2003, Zhao et al 2006. However, this is the first report indicating expression of GILZ in the neuroendocrine system of any species.…”
Section: Discussionmentioning
confidence: 76%
“…Subsequently, GILZ has been shown to be widely expressed and has been detected in numerous tissues and cell types , Berrebi et al 2003, Kolbus et al 2003, Shi et al 2003, Zhao et al 2006. GILZ is thought to be a transcription factor and has been shown experimentally to bind DNA (Shi et al 2003) as well as interact with other leucine zipper transcription factors such as c-Fos and c-Jun (Mittelstadt & Ashwell 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixteen-micrometer cryostat sections through the uteri were collected and thaw-mounted onto Superfrost plus slides. The slides were vacuum dried overnight and stored at -80°C [28]. RNA probes were prepared with α- 33 P-uridine triphosphate (Perkin Elmer, NJ) by incubating 2 μg of the linearized template with the appropriate polymerase using the Promega Riboprobe System [29].…”
Section: Methodsmentioning
confidence: 99%
“…Upon GC stimulation, expression of GILZ increases in lymphocytes, especially in monocytes and macrophages (Chen et al, 2006). GILZ may mediate the activation of T-cell receptor, inhibit the expression of Fas/FasL and IL-2 in lymphocytes, modulate T-cell activation and apoptosis, inhibit the activation of Raf-1, and be involved in the stress reaction of endothelial cells (Bhalla et al, 2006;Brennan and Fuller, 2006;Zhao et al, 2006;Reineke et al, 2007). Previous studies found that GILZ may promote the expression and activation of GR by weakening the inhibitory effects of transcription inhibitors and pro-inflammatory cytokines on GR, thereby reducing to some degree GC resistance (Sun et al, 2002).…”
Section: Introductionmentioning
confidence: 99%